2015
DOI: 10.1021/acsphotonics.5b00433
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Collection of Light from Colloidal Quantum Dots with a Hybrid Metal–Dielectric Nanoantenna

Abstract: We introduce a hybrid metal−dielectric nanoantenna consisting of a metallic bullseye nanostructure and a dielectric waveguide layer, for directing the photon emission of embedded colloidal nanocrystal quantum dots. This structure overcomes the intrinsic losses of plasmonic nanoantennas on one hand and is much more scalable than dielectric nanoantennas on the other. The experimental results demonstrate a very low divergence angle beam, allowing a collection efficiency of 30% of the quantum dot emission into a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 25 publications
1
57
0
Order By: Relevance
“…[ 14,15 ] By using properly nanostructured environment, i.e., by coupling QEs with nanocavities or nanoantennas, the QE emission rates can be enhanced drastically due to the Purcell effect. [ 16–19 ] Many efforts have also been dedicated to obtaining high collection efficiency by directing the QE emission with surrounded nanostructures, including Yagi‐Uda antennas [ 20–23 ] and bullseye gratings, [ 24–28 ] demonstrating that highly directional beams can straightforwardly be realized by utilizing different kinds of bullseye structures in forms of concentric ridges. Regarding the single‐photon purity and photon indistinguishability, recent reports have proved that these two parameters can simultaneously reach high levels with properly chosen QEs incorporated at cryogenic temperatures in semiconductor cavities.…”
Section: Figurementioning
confidence: 99%
“…[ 14,15 ] By using properly nanostructured environment, i.e., by coupling QEs with nanocavities or nanoantennas, the QE emission rates can be enhanced drastically due to the Purcell effect. [ 16–19 ] Many efforts have also been dedicated to obtaining high collection efficiency by directing the QE emission with surrounded nanostructures, including Yagi‐Uda antennas [ 20–23 ] and bullseye gratings, [ 24–28 ] demonstrating that highly directional beams can straightforwardly be realized by utilizing different kinds of bullseye structures in forms of concentric ridges. Regarding the single‐photon purity and photon indistinguishability, recent reports have proved that these two parameters can simultaneously reach high levels with properly chosen QEs incorporated at cryogenic temperatures in semiconductor cavities.…”
Section: Figurementioning
confidence: 99%
“…Recent studies on circular plasmonic structures similar to our plasmonic lens have shown a similar spectral dip; yet, the authors ascribed such a dip to either a Fano resonance [24] due to SPP coupling with a waveguiding layer atop the grating (such a layer is absent in our case), or to an instrumental artifact due to the collection geometry (see the supporting information of Ref. [45]).…”
Section: G Spectral Response: Role Of the Slit Gratingmentioning
confidence: 52%
“…A clear understanding of the spectral response of a plasmonic lens in the visible and near-infrared frequency domains is pivotal for future applications. The frequency-dependent response of a plasmonic lens to a local excitation source has been addressed in a few specific cases [9,[21][22][23][24], yet comprehensive studies have been missing up until now. This need is even more urgent with the recent development of novel integrated electrically driven light and SPP nanosources [25][26][27][28], which have an inherently broad power spectrum, and the rapid emergence of new fields in plasmonics that use ultrashort (and thus spectrally broad) light pulses [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, such couplings have been experimentally realized on various systems such as metal‐integrated semiconductor nanowires, [ 1 ] metal‐coated dielectric structures, [ 2 ] microsphere coupled with metallic particles, [ 3 ] dielectric nanospheres placed near metallic film. [ 4,5 ] These hybrid structures have been utilized, to design single photon devices, [ 6–8 ] optical antenna, [ 9,10 ] to tune the photoluminescence dynamics of emitters [ 11,12 ] and for enhanced spontaneous emission from emitters [ 13–15 ] down to the level of single molecule with minimized ohmic losses. [ 16,17 ]…”
Section: Figurementioning
confidence: 99%